Cellular Mechanisms of Tissue Fibrosis. 6. Purinergic signaling and response in fibroblasts and tissue fibrosis - Lu, David (American Physiological Society, 2013)
Tissue fibrosis occurs as a result of the dysregulation of extracellular matrix (ECM) synthesis. Tissue fibroblasts, resident cells responsible for the synthesis and turnover of ECM, are regulated via numerous hormonal and mechanical signals. The release of intracellular nucleotides and their resultant autocrine/paracrine signaling have been shown to play key roles in the homeostatic maintenance of tissue remodeling and in fibrotic response post-injury. Extracellular nucleotides signal through P2 nucleotide and P1 adenosine receptors to activate signaling networks that regulate the proliferation and activity of fibroblasts, which, in turn, influence tissue structure and pathologic remodeling. An important component in the signaling and functional responses of fibroblasts to extracellular ATP and adenosine is the expression and activity of ectonucleotideases that attenuate nucleotide-mediated signaling, and thereby integrate P2 receptor- and subsequent adenosine receptor-initiated responses. Results of studies of the mechanisms of cellular nucleotide release and the effects of this autocrine/paracrine signaling axis on fibroblast-to-myofibroblast conversion and the fibrotic phenotype have advanced understanding of tissue remodeling and fibrosis. This review summarizes recent findings related to purinergic signaling in the regulation of fibroblasts and the development of tissue fibrosis in the heart, lungs, liver, and kidney.